Sistem Aplikasi Kas Untuk Pembukuan Koperasi Ta’awun Berbasis Website Menggunakan Metode Agile - Sekar Asri Andamari; Muhammad Fauzan Gustafi (Universitas Boyolali, 2025)
The Ta'awun Cooperative was established within the Muhammadiyah Metro General Hospital environment. All financial management activities are still carried out manually, which causes a lack of transparency and can lead to errors. Therefore, a digital system is needed to support cash management. This research aims to develop a website-based cooperative cash application system to support the recording of cash inflows, cash outflows, and all existing transactions so that they are easily accessible. This development uses Agile Software Development with the stages of planning, implementation, testing, documentation, deployment, and maintenance. The application was built using PHP (Laravel Framework) with Filament as the admin panel to support data processing and MySQL as the database. This application system is capable of automating the recording of all cash inflows, cash outflows, loan data, payment data, and presenting financial reports in real-time, as well as having an easy-to-use interface. Testing through Black Box Testing and User Acceptance Testing (UAT) showed that the system functions as expected and is well received by cooperative administrators because it is easy to use and improves recording efficiency. This system is a solution for cooperatives undergoing digitalization, while also supporting modern, accountable, and transparent governance.